2005
DOI: 10.1007/s10637-005-2899-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-erbB-2 antibody trastuzumab in the treatment of HER2-amplified breast cancer

Abstract: Human epidermal growth factor receptor-2 (HER2/erbB-2) is a member of a family of four transmembrane receptor tyrosine kinases that regulate cell growth, survival and differentiation via multiple signal transduction pathways. Amplification of the HER2 gene occurs in 20-25% of human breast cancers. This amplification event is an independent adverse prognostic factor as well as a predictive factor for increased response to doxorubicin-based combination chemotherapy, response to trastuzumab and decreased response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
49
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(55 citation statements)
references
References 108 publications
0
49
0
4
Order By: Relevance
“…Such strategies include the use of monoclonal antibodies, for example trastuzumab (5) and pertuzumab (6) or degradation of HER2 expression (7). The humanized monoclonal antibody trastuzumab has confirmed clinical efficacy for treatment of breast cancer and has been accepted for routine clinical use (8). Apparently, such therapy can be efficiently used only for patients with tumors expressing HER2.…”
Section: Introductionmentioning
confidence: 99%
“…Such strategies include the use of monoclonal antibodies, for example trastuzumab (5) and pertuzumab (6) or degradation of HER2 expression (7). The humanized monoclonal antibody trastuzumab has confirmed clinical efficacy for treatment of breast cancer and has been accepted for routine clinical use (8). Apparently, such therapy can be efficiently used only for patients with tumors expressing HER2.…”
Section: Introductionmentioning
confidence: 99%
“…Herceptin in combination with cisplatin, paclitaxel, docetaxel, gemcitabine and vinorelbine have shown promising clinical results (Yeon and Pegram, 2005;Nahta and Esteva, 2006). The theory is that combining Herceptin with other biological targeting agents may increase the extent of the patient response.…”
mentioning
confidence: 99%
“…The theory is that combining Herceptin with other biological targeting agents may increase the extent of the patient response. Some of the newer novel combinations include Herceptin plus anti-EGFR tyrosine kinase inhibitor gefitinib (Iressa), lapatinib (Tarceva), a combined EGFR/ErbB2 inhibitor lapatinib (GW572016), cyclin-dependent kinase inhibitor flavopiridol, VEGF inhibitor becacizumab (Avastin) and Interleukin inhibitors (Yeon and Pegram, 2005;Nahta and Esteva, 2006).…”
mentioning
confidence: 99%
“…The methods used for selecting patients for trastuzumab therapy are immunohistochemical (IHC) and gene-based FISH analysis of primary tumor. Retrospective studies have shown that measurement of gene amplification is the best predictive marker of response to trastuzumab-based therapy (4)(5)(6).…”
mentioning
confidence: 99%